Analisis Saluran Distribusi dan Margin Pemasaran Telur Itik di Kabupaten Situbondo - Latifatul Hasanah; Ujang Suryadi; Wahjoe Wihijanto (Politeknik Negeri Jember, 2017)
This study aims to find out the distribution and marketing margins of duck eggs in Situbondo. The methods used to collect data were survey and interviews suported by questionnaires. The analisys of Â short and long distribution channels showed were 2.84% and 1.16% respectively. The short distribution channel was more efficient than long distributin channel, so that it provided greater benefits for marketing of duck eggs in Situbondo.